The zebrafish as a model for paediatric diseases. (7th September 2012) - Lohi, Olli; Parikka, Mataleena; Rämet, Mika
Abstract The rapid increase in information about genes and their associations with human diseases has highlighted the need for model organisms suitable for genetic manipulation and drug testing. The zebrafish is a valuable vertebrate animal model that offers many advantages, including the relative ease of husbandry and genetic manipulation and the capacity for high‐throughput screens. In this review, we describe the zebrafish as a model for paediatric diseases, with particular emphasis on haematopoietic and infectious diseases. Conclusion: The zebrafish has become an established vertebrate model in which to elucidate the molecular mechanisms of various human diseases.